Festival Stakeholder Strategic Mapping: Power-Interest Matrix Analysis for Cap Go Meh Singkawang Inclusive Governance - Tohirin, Ahmad; Widianingsih, Ida; Pancasilawan, Ramadhan (International Journal of Artificial Intelligence Research, 2025)
This study aims to analyze the power-interest configuration of stakeholders in the governance of the Cap Go Meh Singkawang Festival to assess the level of inclusivity and formulate appropriate engagement strategies. The research employs a qualitative case study method, collecting data through in-depth interviews, participatory observation, and document analysis involving seven key stakeholder groups. Findings reveal a tripartite dominance of the Festival Committee, Cultural Community, and Sponsors as Key Players with high power and interest. At the same time, MSME actors and affected residents are marginalized as Subjects with high dependency but low influence. This configuration reflects an elitist and less inclusive governance model. Based on these findings, the study recommends reconstructing the collaborative architecture through a more representative festival board, reforming data-based economic participation systems, and developing a long-term collaborative ecosystem that empowers marginalized groups. This research suggests a systematic redistribution of power to achieve more equitable and sustainable festival governance.